2017
DOI: 10.1016/j.jot.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Danger of frustrated sensors: Role of Toll-like receptors and NOD-like receptors in aseptic and septic inflammations around total hip replacements

Abstract: The innate immune sensors, Toll-like receptors (TLRs) and nucleotide-binding oligomerization domain (NOD)-like receptors (NLRs), can recognize not only exogenous pathogen-associated molecular patterns (PAMPs), but also endogenous molecules created upon tissue injury, sterile inflammation, and degeneration. Endogenous ligands are called damage-associated molecular patterns (DAMPs), and include endogenous molecules released from activated and necrotic cells as well as damaged extracellular matrix. TLRs and NLRs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 207 publications
(253 reference statements)
0
21
0
Order By: Relevance
“…24 Nearly all kinds of the most popular prosthetic materials nowadays have been proved to produce wear particles which activate the immune system and finally cause aseptic loosening. 4 Even though materials like ceramics and highly cross-linked polyethylene (HXLPE) have been widely used to reduce the wear of prostheses, it is still vital to clarify the mechanism of aseptic loosening. In our previous studies, types and sizes were defined as the most important factors for the biological characteristics of wear particles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Nearly all kinds of the most popular prosthetic materials nowadays have been proved to produce wear particles which activate the immune system and finally cause aseptic loosening. 4 Even though materials like ceramics and highly cross-linked polyethylene (HXLPE) have been widely used to reduce the wear of prostheses, it is still vital to clarify the mechanism of aseptic loosening. In our previous studies, types and sizes were defined as the most important factors for the biological characteristics of wear particles.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that wear particles from the prosthesis, inducing macrophage activation and finally leading to peri-prosthesis osteolysis, were the predominant cause of aseptic loosening. 4 It has been reported that sub-micron zirconium dioxide particles in a polymethylmethacrylate matrix released from bone cements were most abundant in tissue around cemented stems, while pure Ti and Ti alloy elements were mostly detected near uncemented cups. Polyethylene particles accounted for only a small part of the total number of particles around the prosthesis.…”
Section: Introductionmentioning
confidence: 99%
“…This difference may be due to differences in cell types (peritoneal macrophages in Samelko et al vs. BMDM in the present study), or due to potential differences in the FBS used in the culture medium (unspecified grade of FBS in Samelko et al vs. ultra-low endotoxin FBS in the present study). In any case, it should be noted that in vivo , priming may also be achieved by endogenous factors or alarmins [ 67 69 ], by ions directly binding to a TLR or through PAMP (including LPS) originating from a subclinical bacterial biofilm on the implant material surface [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 TLR4 is a PRR on the cell surface, and is activated by PAMPs, DAMPs, and other substances. 29 TLR4 has two signaling pathways: the MyD88 dependent (TLR4/MyD88/NF-κB) pathway and the MyD88 independent (TLR4/TRIF/IRF3) pathway. 30 The MyD88 dependent pathway activates NF-κB and promotes the expression of MCP-1, a chemokine.…”
Section: Relationship Between Chronic Inflammation and Osteonecrosismentioning
confidence: 99%